ANDROID-BASED VIRTUAL LABORATORY DEVELOPMENT (CASE STUDY OF CLASS XI OF SMA IN BANDAR LAMPUNG) - Saepulloh, Dede; Gunawan, Indra; Agustin, Siti Amalia (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aims to develop an android-based virtual laboratory e-module learning media in class XI thermodynamics material which aims to determine the process of developing e-modules, determine the feasibility of e-modules and determine the response of educators and students to the e-modules developed. The type of research is Research and Development (R&D). This research refers to the ADDIE model procedure. The results of the research carried out that the development of an android-based virtual laboratory e-module on thermodynamic material assessments from material experts and media experts obtained a very feasible category with 90% validation percentage of material experts, and 88% of media experts. The questionnaires given by the response of educators and participants to the developed e-module were 90%, small group trials received 92% and field trials scored 92%. This shows that the android-based virtual laboratory e-module on class XI thermodynamics material that has been developed is very feasible and interesting to use as a learning medium.